PENGARUH PENAMBAHAN ZIRKONIUM OKSIDA DAN SERAT POLIPROPILEN TERHADAP KEKUATAN IMPAK DAN TRANSVERSAL BAHAN BASIS GIGI TIRUAN RESIN AKRILIK POLIMERISASI PANAS - Eddy Dahar; Raudhatul Husna (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2017)
Heat polymerized acrylic resin is the most common material used for making denture base because of it’s advantages. However, this material still hasn’t fulfill all the ideal requirements as a denture base. Some disadvantages that need to be fixed are low impact and transverse strength causing an easy base of fracture. Several attempts were made to improve the mechanical properties of heat polymerized acrylic resin materials by adding reinforcing materials. Zirconium oxide is one of chemical group that can be used as a reinforcing material and polypropylene fiber which is including in fiber reinforcing groups. This study aims to determine whether there is a difference in the effect of the addition of 5% ZrO2 nanoparticles and 2% chopped polypropylene fibers 6 mm in length on the impact and transverse strength of heat polymerized acrylic resin denture base material. The design of this study is a laboratory experimental and the number of samples in this study are 60 samples. The result of this study shows the mean value of the impact and transverse strength of heat polymerized acrylic resin with ZrO2 nanoparticles reinforced is greater than the control group and heat polymerized acrylic resin group with polypropylene fiber reinforced with significant difference, and the mean value of impact and transverse strength of heat polymerized acrylic resin with polypropylene fibers reinforced is greater than the control group with significant difference.